Development of a Chemistry E-Module Based on a Problem Based Learning Model on Reaction Rate Material - Harahap, Armita Sari; Yusuf, Muhammad (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
The lack of students’ high-level thinking abilities regarding the materials taught, especially the buffer solution material, is because the buffer solution material is one of the materials that is difficult for students to understand, some teachers who teach still seem monotonous, resulting in reduced interest in learning for students, and the students Students experience boredom if learning uses inadequate media. To determine the validity, practicality and effectiveness of using E-Module learning media based on Higher Order Thinking Skills (HOTS). The type of research used in this research is Research & Development (R&D) or development research. Development research that refers to the 4-D (four-D) model. The steps of the 4-D (four-D) development model consist of 4 development stages but researchers only use 3 stages, namely define, design, and develop. The subjects in this research were 1 media expert, 2 material experts, 1 practical test teacher, and 30 students tested. The media expert validation results were 93% and the material expert validation results were 83.33% in the “Very Valid” category. The results of the practicality test by the teacher obtained a percentage of 82% in the “Very Practical” category. The trial with 30 students obtained a percentage result of 86.33% in the “Very Effective” category. It can be concluded that the development of an E-Module based on Higher Order Thinking Skills (HOTS) on buffer solution material is declared to be very valid, practical and effective for use as a learning medium.Keywords: Development Research, E-Modul, Hots, Buffer solutionDOI: 10.23960/jppk.v13.i3.31664